2007
DOI: 10.1044/0161-1461(2007/033)
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Language Skills of Adjudicated and Nonadjudicated Adolescent Males and Females

Abstract: As the majority of adjudicated adolescents had not been previously identified as having difficulties with language abilities, this population could benefit from early assessment. Also, children who are at risk for incarceration should be screened for possible language deficits that could contribute to the many difficulties experienced by adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…However, this preliminary evidence has not been replicated in other studies that have specifically looked at language differences. A study considering the language differences between adjudicated and non‐adjudicated adolescents, for example, reported a between‐group difference but no within‐group gender differences (Blanton & Dagenais, ). In order to provide further insight into potential gender differences in youth offenders and address the available mixed evidence based on very small sample sizes in previous studies, we include, to the best of our knowledge, the largest sample of female young offenders in the United Kingdom (UK), to provide evidence of the point prevalence of DLD in females and examine gender differences in the psycholinguistic and socioemotional profiles of young offenders.…”
Section: Introductionmentioning
confidence: 99%
“…However, this preliminary evidence has not been replicated in other studies that have specifically looked at language differences. A study considering the language differences between adjudicated and non‐adjudicated adolescents, for example, reported a between‐group difference but no within‐group gender differences (Blanton & Dagenais, ). In order to provide further insight into potential gender differences in youth offenders and address the available mixed evidence based on very small sample sizes in previous studies, we include, to the best of our knowledge, the largest sample of female young offenders in the United Kingdom (UK), to provide evidence of the point prevalence of DLD in females and examine gender differences in the psycholinguistic and socioemotional profiles of young offenders.…”
Section: Introductionmentioning
confidence: 99%
“…People with language impairments are overrepresented in our courts and prisons (Blanton & Dagenais, 2007; Kavanagh, Rowe, Hersch, Barnett, & Reznik, 2010). In fact, the majority of prisoners in the United States have language impairments that are either acquired (see Shiroma, Ferguson, & Pickelsimer, 2010, for a review) or developmental (Bryan, Freer, & Furlong, 2007; Sanger, Hux, & Belau, 1997).…”
mentioning
confidence: 99%
“…Another UK-based analysis (Barrett et al, 2006) reported that an estimated £1000 million per year is spent on "processing and dealing with young offenders" (p. 541 Research in Australia (Snow & Powell, 2004a,b;2005; has contributed to a small but growing body of international research on the oral language skills of young offenders. These studies, together with work from the USA (e.g., Blanton & Dagenais, 2007;Sanger, Moore-Brown, Magnuson & Svoboda, 2000) and the UK (Bryan, 2004;Bryan, Freer & Furlong, 2007) show that in addition to being socially and educationally marginalised, young offenders (particularly males) are at high risk of experiencing unrecognised oral language impairments, as evidenced by significantly compromised performance on standardised language measures when compared with 8 controls of similar ages and demographic backgrounds. Snow and Powell (2008) found that over 50% of a sample of young offenders on community orders could be classified as language impaired, using measures of comprehension and verbal expression, particularly where these were sensitive to the processing and manipulation of abstract language.…”
Section: Table Of Contentsmentioning
confidence: 92%